Investigating the process of patient flow and identifying opportunities for its improvement based on lean management using the Six Sigma approach in the emergency department - Mahmoud Nekoei Moghadam; Mohammad Hossein Mehrolhassani; Rohaneh Rahimisadegh; Azam Parvaz (Tehran University of Medical Sciences, 2024)
Background & Aim: Given the importance of the emergency department in providing prompt and high-quality services, the emphasis on lean management has increased to minimize non-value-added and wasteful activities within a process. The aim of the study was to determine the process of patient flow and identify opportunities for its improvement using the Six Sigma method as one of the most important subsystems of lean management, in the emergency department of the selected teaching hospital in Kerman. Methods & Materials: The current research is a sequential mixed-method study conducted in 2022 within the cardiovascular and neurological emergency department in Kerman. The Six Sigma method, specifically the DMAIC approach consisting of four steps, was employed in conjunction with spaghetti charts to implement lean management principles. The research population included 180 patients referred to the cardiovascular and neurological emergency department. The data were collected using researcher-developed forms, and Excel software version 2013 was used to analyze the data. Results: By examining the processes and using the spaghetti chart, the main problems contributing to prolonged patient admission time in the cardiology and neurology emergency department were identified. The implementation of a strategy involving the presence of admission staff during triage for level 1 to 3 patients will eliminate the additional distance and time required for patient admission. Conclusion: The use of lean thinking principles in the emergency department with the implementation of Lean Six Sigma and Spaghetti Chart by streamlining the service process, will result in improving patient flow, providing timely quality services, reducing service delivery time, and ultimately increasing patient satisfaction.